In Vitro evaluation of the anti-pancreatic cancer activity of epimedium herb - Yangfeng Chen; Han Xia; Xiaohong Zhong (Frontiers Media S.A., 2024)
Introduction: Pancreatic cancer (PC) is a particularly aggressive malignancy with limited therapeutic options. The search for innovative treatments has focused on traditional Chinese medicine, specifically epimedium. This research investigates epimedium's active ingredients, potential targets, and underlying mechanisms in treating PC.Methods: High-performance liquid chromatography (HPLC) was used to quantify the active components of epimedium and HPLC-Q-TOF-MS was employed for qualitative identification. Potential targets of epimedium's active ingredients were identified using the TCMSP, ETCM, CTD, and Swiss Target Prediction databases. Potential PC-related targets were sourced from DisGeNET, GeneCards, and OMIM databases. A Venn diagram was utilized to identify overlapping PC-related and epimedium targets. Core targets and pathways were elucidated through protein-protein interaction (PPI) network analysis, Gene Ontology (GO) assessments, and Reactome pathway enrichment analyses. Molecular docking techniques investigated interactions between active compounds and these targets. The expression and prognostic implications of target genes were evaluated using GEPIA2 and the Human Protein Atlas (HPA) databases. In vitro studies assessed the impact of epimedium extract (EPE) on Panc-1 cell viability, and Western blot analysis examined the expression levels of key targets.Results: Network pharmacological indicate that epimedium econtains active components such as baohuoside I, icariin, hyperoside, and epimedin B, which have potential therapeutic effects against PC. In vitro assays confirmed that EPE significantly reduced the viability of Panc-1 cells. Western blot analysis revealed a considerable decrease in the expression of key targets in EPE-treated cells, including AKT1, EGFR, p-EGFR, JUN, BCL2, IL6, and SRC. The R-HSA-1280215: Interleukin-4 and Interleukin-13 signaling pathways involving these genes were identified as potential therapeutic targets.Discussion:Epimedium holds promise as a candidate for treating PC. The modulation of interleukin-4 and interleukin-13 signaling pathways could be a pivotal mechanism by which epimedium impedes tumor development. Further research is warranted to validate these findings and explore the clinical applicability of epimedium in PC treatment.